Фольклор і фольклористика – традиція чи сучасність - Велев, І. (Народна творчість та етнографія, 2009)
The article gives a new viewpoint on understanding folklore. First of all it is presented as a form of national identity and individual perception of the world. The author suggests that different kinds of spiritual and creative levels form a great number of layers. The correlation between folklore and modern concepts of globalization of cultures is researched.